1996
DOI: 10.1002/art.1780391207
|View full text |Cite
|
Sign up to set email alerts
|

Presence of antibodies to native G1 domain of aggrecan core protein in synovial fluids from patients with various joint diseases

Abstract: Objective. To investigate the occurrence of IgG antibodies to aggrecan in synovial fluids (SF) from patients with arthritis and various articular diseases, and to determine the nature of epitopes present within aggrecan that react with these antibodies. Methods. SF samples were reacted with native aggrecan, reduced and alkylated aggrecan, chondroitin sulfate, and keratan sulfate, using dot‐blots and a novel enzyme‐linked immunosorbent assay (ELISA). The nature of the epitopes present on aggrecan was elucidated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Among others, such as collagens,9 human cartilage glycoprotein-39 (HC-gp39),10 link protein,11 12 human cartilage proteoglycan aggrecan (PG) might be an autoimmune target 13 14 15. Indeed, immune responses to PG and a few T-cell epitopes have been detected in patients with RA, juvenile idiopathic arthritis, osteoarthritis and ankylosing spondylitis12 13 14 16 17 18 19 20 supporting the hypothesis.…”
mentioning
confidence: 67%
“…Among others, such as collagens,9 human cartilage glycoprotein-39 (HC-gp39),10 link protein,11 12 human cartilage proteoglycan aggrecan (PG) might be an autoimmune target 13 14 15. Indeed, immune responses to PG and a few T-cell epitopes have been detected in patients with RA, juvenile idiopathic arthritis, osteoarthritis and ankylosing spondylitis12 13 14 16 17 18 19 20 supporting the hypothesis.…”
mentioning
confidence: 67%
“…Anti-CCP antibodies were detected in 7 out of 136 OA patients [129], while another group also detected them in OA patients but at significantly lower levels compared to RA patients [130]. Antibodies against native G1 domain of aggrecan core protein were found in synovial fluid of OA patients [131]. Using proteomic approach, Xiang et al identified triosephosphate isomerase (TPI) as an important antigen with autoantibodies present specifically in OA but not in RA [127].…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Cell-mediated immune reactivity to cartilage PG was shown in patients with OA (21). The frequent occurrence of IgG antibodies to the native G1 domain of PG was found in the synovial fluid of OA patients (22). Recently, we demonstrated the presence of cellular immune reactions to LP and the G1 domain in patients with different inflammatory arthritides (23)(24)(25)(26).…”
mentioning
confidence: 93%